2020
DOI: 10.3390/su12114463
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility towards the Environment in Lublin Region, Poland: A Comparative Study of 2009 and 2019

Abstract: Today’s businesses have a huge impact on the environment. Enterprises overuse available natural resources, and emit hazardous pollutants; thus, they contribute to the advancing degradation of existing ecosystems, causing serious threats to the biological diversity of our planet. Hence, there is an urgent need to undertake diverse actions to reduce the adverse impact of businesses, households, and whole societies on the environment, and stop its degradation. The goal of this paper is to present research finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 37 publications
0
28
0
2
Order By: Relevance
“…Some CSR issues are focused on community, corporate governance, public -private partnerships, and prosperity. The most common reasons, why companies do not implement CSR in V4 countries are: lack of employees with relevant knowledge in this area, lack of information or benefits from the government, or lack of company's financial resources (Zelazna et al, 2020;Nagypál, 2014;Slabá, 2020;Lušňáková et al, 2019). Li et al (2020) highlighted that most of the studies are focused on companies' financial performance.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Some CSR issues are focused on community, corporate governance, public -private partnerships, and prosperity. The most common reasons, why companies do not implement CSR in V4 countries are: lack of employees with relevant knowledge in this area, lack of information or benefits from the government, or lack of company's financial resources (Zelazna et al, 2020;Nagypál, 2014;Slabá, 2020;Lušňáková et al, 2019). Li et al (2020) highlighted that most of the studies are focused on companies' financial performance.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Clerici et al [12] show how deforestation is affecting Colombian protected areas during post-conflict periods and how the leading role of communities, their leadership, and organization, are starting points to contribute to solving this problem. Zelazna et al [13] and Esteban-Salvador et al [14] describe the most frequent environmental activities carried out by companies operating in the Lublin region (Poland) and rural areas of Spain, respectively, aimed at protecting the environment. In addition, Barclay and Barker [15] showed how environmentalism contributes to the recognition of how people see the value in others, and therefore, contributes to the intention of carrying out collective and collaborative actions.…”
Section: Introductionmentioning
confidence: 99%
“…A. Zelazna, M. Bojar and E. Bojar [9] showed that social responsibility associated with conducting economic activities in compliance with environmental protection requirements for local enterprises makes it possible to implement the principles of sustainable development and introduce environmental management. Enterprises responsibly analyze their impact on the use of a variety of resources in production activities and look for solutions that minimize the environmental burden on the company's activities.…”
Section: Resultsmentioning
confidence: 99%